2014
DOI: 10.1037/a0036858
|View full text |Cite
|
Sign up to set email alerts
|

When speech sounds like music.

Abstract: Repetition can boost memory and perception. However, repeating the same stimulus several times in immediate succession also induces intriguing perceptual transformations and illusions. Here, we investigate the Speech to Song Transformation (S2ST), a massed repetition effect in the auditory modality, which crosses the boundaries between language and music. In the S2ST, a phrase repeated several times shifts to being heard as sung. To better understand this unique cross-domain transformation, we examined the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
87
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 127 publications
(173 reference statements)
7
87
2
Order By: Relevance
“…By listening to a spoken phrase several times, listeners perceive the phrase as sung. This simple and compelling experiment suggests that the categorization of a performance as speech or song does not rely on the acoustical characteristics (always the same) but rather on the repetition effect leading to the reinterpretation of the material as musical (Falk et al, 2014). However, when listening to a single sound or isolated phrase (i.e., not repeated and without previous exposition to the phrase), listeners are able to detect a clear spoken or sung utterance (Merrill et al, 2016) and therefore rely on acoustical parameters of the signal itself or on perceptual impressions.…”
Section: Introductionmentioning
confidence: 99%
“…By listening to a spoken phrase several times, listeners perceive the phrase as sung. This simple and compelling experiment suggests that the categorization of a performance as speech or song does not rely on the acoustical characteristics (always the same) but rather on the repetition effect leading to the reinterpretation of the material as musical (Falk et al, 2014). However, when listening to a single sound or isolated phrase (i.e., not repeated and without previous exposition to the phrase), listeners are able to detect a clear spoken or sung utterance (Merrill et al, 2016) and therefore rely on acoustical parameters of the signal itself or on perceptual impressions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of flat pitches, therefore, may be one of the cues which primes the speech-to-song illusion (henceforth, "song illusion"). Recent work by Falk, Rathcke, & Dalla Bella (2014) has presented evidence that pitch contour variability has a causal effect on the magnitude of the song illusion: flattening the pitch contour between tonal targets--the pitch targets hypothesized by autosegmental approaches to intonation (Ladd, 2008)--led to earlier and more frequent reports of song transformations for two German sentences. However, the resulting artificially flat pitch contours are uncharacteristic of natural speech, which leaves open the question of whether within-syllable pitch variability can explain variance in the song illusion among naturalistic stimuli, as well as whether a more subtle manipulation could modulate the song illusion.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that the song illusion causes listeners to hear syllable pitches in terms of musical scale tones, a process which may be facilitated if a stimulus' pitches are an easier fit to a musical key template. Yet Falk et al (2014) found that changing two pitch intervals into perfect fifths (a pitch interval which forms a backbone of scale structure in many cultures) had only a trending effect on the frequency of reports of the song illusion, and thus the role of melodic structure in driving the song illusion remains in question. Here we investigate this possibility by comparing the magnitude of the song illusion with the extent to which each phrase's sequence of pitches fits a computational model of melodic structure (Temperley, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations